Zahora, a new monotypic genus from tribe Brassiceae (Brassicaceae) endemic to the Moroccan Sahara - Koch, Marcus; Lemmel, Claude (PhytoKeys, 2019)
Zahora ait-atta Lemmel & M.Koch, a new species from the Moroccan Sahara, is described and documented here and constitutes a monotypic new genus. The new taxon belongs to the tribe Brassiceae (Brassicaceae), and cytogenetic and phylogenetic analyses reveal that this diploid species has a remote status of Miocene origin in the northwestern Sahara Desert. We examined the morphological differences between morphologically related genera and provide photographs of the new species. The new genus may play a key role in future Brassica-Raphanus crop research since it is placed phylogenetically at the base of a generically highly diverse clade including Raphanus sativus, and it shows affinities to various Brassica species.